Big Data Analytics in the Algorithmic Management Process: The Case of Transport Platforms in the Gig Economy - Nowik, Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Gig economy business models are based on the mass automation of management decisions and workplace surveillance, which require using vast amounts of data and conditioning the algorithmic management system to function optimally. As a result, data has become an increasingly valuable and strategic economic resource. Ride-hailing platforms were a pioneer in this area. The privacy policies of transport platforms such as Bolt, Uber, and Deliveroo specify the use of data to train machine learning algorithms, which form the basis of automated decision-making. The accumulation of data and the asymmetry of information on these platforms leads to a serious violation of privacy rights. As companies collect more and more data about us, we lose control over how that data is used. This issue was highlighted a few years ago by Professor Shoshana Zuboff, who used the term “surveillance capitalism”. Within its framework, the human rights category of the right to privacy becomes the new free raw material for producing behavioural data, and the current article aims to analyse this phenomenon.